2010
DOI: 10.1007/s10535-010-0027-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of chlorophyll fluorescence and antioxidative system in super-hybrid rice and its parental cultivars under chilling stress

Abstract: Characteristics of chlorophyll fluorescence and antioxidative system were investigated in rice (Oryza sativa L.) super-hybrid Liangyoupeijiu (LYPJ), maternal cultivar Peiai64s, and paternal cultivar indica rice 9311 under chilling stress. During 6-d chilling treatment, chlorophyll content of all three genotypes was gradually declined. However, the decrease in photosystem 2 (PS 2) maximum photochemical efficiency (F v /F m ) and quantum yield of PS 2 (Φ PS2 ) was less expressive in LYPJ than in parental cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
2
18
1
Order By: Relevance
“…We also found that non-photochemical quenching was signifi cantly increased by water defi cit (Fig. 2H), indicating an increase in thermal dissipation compensating the reduced photochemical dissipation (Zhang et al, 2010). Higher non-photochemical quenching at 25%FC in XN889 than in CY17 may be associated with its larger Fv/ Fm, which indicated that the damage to PSII in XN889 was less than that in CY17.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…We also found that non-photochemical quenching was signifi cantly increased by water defi cit (Fig. 2H), indicating an increase in thermal dissipation compensating the reduced photochemical dissipation (Zhang et al, 2010). Higher non-photochemical quenching at 25%FC in XN889 than in CY17 may be associated with its larger Fv/ Fm, which indicated that the damage to PSII in XN889 was less than that in CY17.…”
Section: Resultsmentioning
confidence: 76%
“…Reduction of Fv/Fm and Fv/Fo (Fig. 2D, E) indicated damage to an important portion of the PSII reaction center (Zhang et al, 2010). ΦPSII and ETR decreased under water defi cit conditions (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Decreased photochemical efficiency of photosystem II due to negative chilling effect is frequently expressed as variable to maximum fluorescence ratio (F v /F m ) (Zhou and Guo 2009). As a consequence of chilling stress, the excess of excitation energy is not promptly quenched and in turn accelerates the formation of reactive oxygen species (ROS), resulting in the reduction of the photosynthetic efficiency (Zhang et al 2010).…”
mentioning
confidence: 99%
“…Chilling and acclimation treatments did not affect maximum quantum yield of PS II (F v /F m ) in 'Sabalan', while caused a significant reduction of F v /F m in 'Zagros' (Table 1). It is well documented that photosynthetic apparatus is sensitive to several environmental stresses and PS II appears to be preferentially affected by chilling stress (Zhang et al, 2010). Reduction of F v /F m in 'Zagros' indicated either damage to PS II or reversible and photoprotective photoinhibition via down-regulation of PS II (Rosenqvist and van Kooten 2003).…”
Section: Resultsmentioning
confidence: 99%